2021
DOI: 10.1021/acssuschemeng.0c06715
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenolysis of Lignin-Derived Aromatic Ethers over Heterogeneous Catalysts

Abstract: Global temperature has risen >1 °C since the preindustrial era, resulting in well-documented adverse climate impacts including extreme weather (floods, droughts, storms, and heat waves), a rise in sea level accompanying melting polar and glacial ice, and disrupted crop growth. These changes are closely correlated with anthropogenic greenhouse gas emissions, predominantly arising from the combustion of nonrenewable fossil fuels. Lignin derived from lignocellulose is the second most abundant biopolymer on Earth,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 178 publications
3
49
0
Order By: Relevance
“…When isopropanol was utilized as the solvent in the reaction, 2-phenoxy-1-phenylethan-1-ol was completely converted and the yields of ethylcyclohexane (95%) and cyclohexanol (92%) reached the maximum. Secondary alcohols provided higher activity, with isopropanol being the most effective, whereas primary alcohols (methanol and ethanol) poisoned catalysis through some absorption of the alkoxy anions . The same result was confirmed in our previous research. In comparison, other solvents were employed in the reaction.…”
Section: Results and Discussionsupporting
confidence: 80%
“…When isopropanol was utilized as the solvent in the reaction, 2-phenoxy-1-phenylethan-1-ol was completely converted and the yields of ethylcyclohexane (95%) and cyclohexanol (92%) reached the maximum. Secondary alcohols provided higher activity, with isopropanol being the most effective, whereas primary alcohols (methanol and ethanol) poisoned catalysis through some absorption of the alkoxy anions . The same result was confirmed in our previous research. In comparison, other solvents were employed in the reaction.…”
Section: Results and Discussionsupporting
confidence: 80%
“…A feasible alternative strategy is catalytic transfer hydrogenation (CTH), [6] in which an internal hydrogen donor provides a reactive source of hydrogen in liquid phase. [7] For example, Guan et al reported the CTH of an α-O-4 model compound 4-(benzyloxy)phenol and lignin extracted from bioconverted rice straw over Pt/HNbWO 6 /CNTs catalyst using isopropanol as the solvent and in-situ hydrogen donor. [8] Light alcohols (methanol, ethanol, and isopropanol) are the most common solvents for CTH due to their ability to solvate/ disperse lignin degradation products and donate hydrogen atoms, [8,9] thereby conferring excellent CTH performance.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the requirement for high pressures of gaseous hydrogen during lignin HDO imposes significant reactor cost and safety constraints and requires a source of sustainable (green) H 2 . A feasible alternative strategy is catalytic transfer hydrogenation (CTH), [6] in which an internal hydrogen donor provides a reactive source of hydrogen in liquid phase [7] . For example, Guan et al.…”
Section: Introductionmentioning
confidence: 99%
“…The catalytic transfer hydrogenation (CTH) or MPV refers to the addition of hydrogen molecules to the unsaturated groups of organic compounds in the presence of a solid catalyst [26][27][28], which does not require external hydrogen or special catalytic hydrogenation equipment and is easy to operate, occupying a certain position in organic synthesis [29][30][31]. Therefore, the CTH reaction is recognized as a versatile method for upgrading bio-based carbonyl compounds [32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%